Forecasting systems for e-government. (5th January 2005) - Nikolopoulos, K.; Patrikakis, C.Z.; Lin, B.
The term e-government refers to the use by government agencies of information technologies that have the ability to upgrade relations with citizens, businesses, and other arms of government. So far, most e-government activity has focused on publishing information via the internet rather than actively interacting with citizens (G2C) or business enterprises (G2B). Forecasting is undoubtedly one of the key processes in operations management and is based on sufficient historic data. Government is the key holder of the majority of crucial databases in the market and projections of those data are pretty important. Thus, forecasting systems are more than necessary for an effective government. Sectors such as healthcare management, real estate market, and financial markets are in great need of adequate forecasts. In the 21st century, e-forecasting replaces traditional forecasting and evangelises an indispensable part of e-government in a rapidly changing cyber world. This study presents a survey on the available bibliography and applications of forecasting systems within the e-government framework and proposes the basic architectural elements of a forecasting system for e-government.